Synthesis and cytotoxic activity of a novel dihydroisoquinoline-derived hydroxamic acid - Ben Salah, Hassen; Carraz, Maëelle; Kammoun, Majed (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Naturally occurring hydroxamic acid derivatives are biosynthesized by microorganisms (siderophores) and plants (benzoxazinoids). Recent developments in drug related research have highlighted the promising biological and pharmacological properties that the hydroxamic acid function may offer for the enhancement of therapeutic applications. This study reports on the full synthesis of a new dihydroisoquinoline hydroxamic acid (2-Hydroxy-3,3-dimethyl-7-nitro-3,4-dihydroisoquinolin-1(2H)-one). It also describes its cytotoxicity with regard to the human hepatocarcinoma cell line Hep3B.